1999
DOI: 10.2337/diabetes.48.12.2463
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological and genetic characterization of the major diabetes locus in GK rats.

Abstract: Genetic studies of the type 2 diabetes-like GK rat have revealed several susceptibility loci for the compound diabetes phenotype. Congenic strains were established for Niddm1, the major quantitative trait locus (QTL) for postprandial glucose levels, by transfer of GK alleles onto the genome of the normoglycemic F344 rat. Despite the polygenic nature of diabetes in GK, the locus-specific diabetes phenotype was retained in the congenic strain Niddmla, containing a GK-derived genomic fragment of 52 cM from the Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
50
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 16 publications
3
50
1
Order By: Relevance
“…This finding is of special importance in the light of previous studies that revealed a major QTL, termed Niddm1, mapping to this same genomic segment on chromosome 1, linked to diabetes in GK rats (25,28). This QTL was later confirmed in congenic strains to be a major factor determining hyperglycemia in GK rats (29), but its role in determining the development of renal disease is unknown. Future studies aiming at dissecting the genetic basis of renal disease in T2DN rats will reveal whether similar genes are responsible for their susceptibility to diabetes and renal disease.…”
Section: Discussionmentioning
confidence: 53%
“…This finding is of special importance in the light of previous studies that revealed a major QTL, termed Niddm1, mapping to this same genomic segment on chromosome 1, linked to diabetes in GK rats (25,28). This QTL was later confirmed in congenic strains to be a major factor determining hyperglycemia in GK rats (29), but its role in determining the development of renal disease is unknown. Future studies aiming at dissecting the genetic basis of renal disease in T2DN rats will reveal whether similar genes are responsible for their susceptibility to diabetes and renal disease.…”
Section: Discussionmentioning
confidence: 53%
“…We conducted our experiments in Goto-Kakizaki (GK) rats for they manifest stable pathological features that resemble human type 2 diabetes with hyperglycemia, basal hypertension, endothelial dysfunction, and development of vascular complications. 20,21 We evaluated in vivo effects of LMWF on blood pressure and local blood flow, ex vivo effects on endothelium-dependent vasodilation and eNOS expression, and in vitro effects of LMWF on eNOS phosphorylation in endothelial cells, and compared them with the effects of probucol, a lipidmodifying drug with powerful antioxidant and antiinflammatory properties used for prevention of type 2 diabetes mellitus. [22][23][24] We found that LMWF profoundly protects endothelial function against the complications of diabetes.…”
mentioning
confidence: 99%
“…In the GK rat model (6,7), a locus for poststimulation glycemia was mapped to a region of rat chromosome 1 syntenic with human 10q23-26 (8,9) and subsequently localized to a 1-cM region around Ide (10). Two amino-acid substitutions in Ide were found in susceptible congenic strains, which, together, conferred postprandial hyperglycemia and reduced insulin degradation in isolated muscle cells, and other diabetes-related phenotypes (10).…”
mentioning
confidence: 99%